A South American Perspective on Antarctic Geopolitics - Portella Sampaio, Daniela; Scott, Shirley V.; Stephens, Tim; McGee, Jeffrey (Springer Nature Singapore, 2024)
Portella Sampaio D. A South American Perspective on Antarctic Geopolitics. In: Scott SV, Stephens T, McGee J, eds. Geopolitical Change and the Antarctic Treaty System. Historical Lessons, Current Challenges . Springer Polar Sciences. Singapore: Springer Nature Singapore; 2024: 311-328. Despite its broad significance for Earth systems, Antarctica has always had more limited political relevance. This limitation is most explicit in relation to the profile of its main actors: the Global North has been a predominant participant in the history of the continent’s regime. A South American perspective offers a counterpoint to this narrative: Argentina, Brazil, Chile, Ecuador, Peru, and Uruguay engage directly in decision-making and provide an alternative to an “unreachable” or “exclusive” Antarctic. Likewise, Colombia and Venezuela demonstrate how new actors are pursuing stronger involvement through regional cooperative ties. Mindful of their diverse Antarctic histories, this chapter discusses South American engagement in Antarctica by focusing on how South American geopolitical thought entitles actors from the global periphery to engage in a once-exclusive region. I first introduce the main assumptions of South America’s geopolitical thought, then briefly recount the individual historical journeys of these South American actors in Antarctica. I demonstrate how South America has organised itself regionally through the creation of institutions, such as RAPAL, and cooperative initiatives between national programmes. I conclude with the potential influence of non-regional actors—such as China and the United States—on the future South American geopolitical imaginary of Antarctica.